In vitro evaluation of the effectiveness of irrigants and intracanal medicaments on microorganisms within root canals - Menezes, M. M.; Valera, M. C.; Jorge, AOC; Koga-Ito, C. Y.; Camargo, CHR; Mancini, MNG (Blackwell Publishing, 2004)
Aim To evaluate in vitro the effectiveness of sodium hypochlorite (NaOCl). chlorhexidine (CHX) and live intracanal medicaments on microorganisms within root canals.Methodology Ninety-six human single-rooted extracted teeth were used. After removing the crowns, canal preparation was completed and the external root Surfaces were coated with epoxy resin. Following sterilization. The teeth were contaminated with Candida albicans and enterococcus faecalis. and were incubated at 37 +/- 1 degreesC for 7 days. The teeth were divided according to the irrigant solution or intracanal medicament: group 1. sterile physiologic solution (SPS) and calcium hydroxide (Ca(OH)(2)) paste: group 2. SPS and camphorated paramonochlorophenol (CPMC): group 3.SPS and tricresol formalin: group 4, SPS and CaOH2 + CPMC paste: group 5, SPS and PMC furacin; group 6.2.5%, NaOCl without intracanal medication: group 7, 2.0% CHX without intracanal medication and group 8, SPS Without intracanal medication (control group). Microbiological samples were collected with sterile paper points, and bacterial growth was determined. The data were submitted to the analysis of variance (ANOVA. P = 0.05).Results For C. albicans, groups 3 and S were statistically less effective than groups 1, 2. 4 and 5 (Kruskal-Wallis (K-W) = 65.241; gl = 7; P = 0.001). For E. faecalis, groups 6 and 8 were statistically less effective than groups 1-4 and 7 (K-W = 61.048; gl = 7; P = 0.001).Conclusions Ca(OH)(2) + CPMC paste was the most effective intracanal medicament for the elimination of the two microorganisms; 2.0% CHX solution was more effective than 2.5% NaOCl against E. faecalis.
Keywords: calcium hydroxide; Candida albicans; chlorhexidine; Enterococcus faecalis; root canal irrigants; sodium hypochlorite